Self-Efficacy of Lecturers and Students in Academic Writing: Are There any Differences? - Safriyani, Rizka; Asmiyah, Siti (IJET (Indonesian Journal of English Teaching), 2023)
Self-efficacy is a critical component of academic article writing. Numerous studies have demonstrated that self-efficacy affects reading comprehension, but few have examined the level of self-efficacy between students and lecturers regarding academic writing. Consequently, this study sought to ascertain students' and lecturers' levels of self-efficacy in academic writing. By administering questionnaires and conducting interviews with students and teachers, this study takes an explanatory mixed-methods approach to the topic. The online survey assesses self-efficacy in academic writing, and students and lecturers complete unstructured interviews. The study enrolled eighty students and eighteen lecturers from the English Department of UIN Sunan Ampel Surabaya. The results indicate that students enrolled in the English Language Education and English Literature Study Programs have a moderate level of self-efficacy. The self-efficacy of lecturers in the English Language Education and English Literature Study Programs demonstrates similar results. Additionally, they are moderate, with a slightly higher average index. This study also discusses the implications of research in the field of education